2002
DOI: 10.5172/conu.12.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life issues identified by palliative care clients using two tools

Abstract: Reported are issues impacting upon the Quality of Life (QoL) of 59 palliative care clients within a district nursing service. These issues reinforce the emerging conceptualisation of QoL as being subjective and multidimensional. The issues were identified during a trial of two QoL assessment and measurement tools, the Client Generated Index (CGI) and the McGill Quality of Life (MQOL). In this era of considerable concern about QoL for the terminally ill, the article's intent is to present the QoL issues identfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The PGI, a personalized measure to identify the impact of specific conditions on QOL [7], has been used and validated in both noncancer populations [7,18] and a variety of cancer populations [9,10,[19][20][21].…”
Section: Personalized Measurementioning
confidence: 99%
“…The PGI, a personalized measure to identify the impact of specific conditions on QOL [7], has been used and validated in both noncancer populations [7,18] and a variety of cancer populations [9,10,[19][20][21].…”
Section: Personalized Measurementioning
confidence: 99%
“…The PGI has been used primarily in noncancerrelated chronic illness populations outside the United States, with only three studies involving patients with cancer (Camilleri-Brennan et al, 2002;Lewis et al, 2002;Llewellyn et al, 2006). Construct validity of the PGI has been evaluated by correlations with other HRQOL measurements, most commonly the SF-36 ® , SF-12 ® , and the QLQ-C30.…”
Section: Validity Of the Patient Generated Indexmentioning
confidence: 99%
“…The third study involved patients receiving palliative care services (Lewis et al, 2002). The authors reported a patient preference for the PGI as opposed to the McGill Quality of Life Questionnaire (Cohen, Mount, Strobel, & Bui, 1995).…”
Section: As Bad As Could Possibly Bementioning
confidence: 99%
See 1 more Smart Citation